ANALYSIS LEARNING MODEL OF DISCOVERY AND UNDERSTANDING THE CONCEPT PRELIMINARY TO PHYSICS LEARNING OUTCOMES SMA - Sri Rosepda Sebayang; Betty M. Turnip (Jurnal Pendidikan Fisika, 2015)
This study aims: 1) to determine whether the student learning outcomes using discovery learning is better than conventional learning 2) To determine whether the learning outcomes of students who have a high initial concept understanding better then of low initial concept understanding, and 3) to determine the effect of interaction discovery learning and understanding of the initial concept of the learning outcomes of students. The samples in this study was taken by cluster random sampling two classes where class X PIA 3 as a class experiment with applying discovery learning and class X PIA 2 as a control class by applying conventional learning. The instrument used in this study is a test of learning outcomes in the form of multiple-choice comprehension test initial concept description form. The results of research are: 1) learning outcomes of students who were taught with discovery learning is better than the learning outcomes of students who are taught by conventional learning, 2) student learning outcomes with high initial conceptual understanding better than the learning outcomes of students with low initial conceptual understanding, and 3) there was no interaction between discovery learning and understanding of initial concepts for the student learning outcomes.